un, self, re, pre ‘KNOW YOURSELF, PROTECT YOUR FUTURE’ AT STATE ISLAMIC JUNIOR HIGH SCHOOL 1 PALANGKA RAYA: A Seminar Report on Promoting Self- Awwareness Among Junior High School Students - Abdul Syahid; sarah, Maisarah; Cahaya Ningrum; Diar Mukti Asri; Nur Lutfiah; Rahmahdalena Putri Khairunnisa (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
The seminar “Know Yourself, Protect Your Future” held at State Islamic Junior High School 1 Palangka Raya aims to provide students with an understanding of the importance of self-awareness and self-care. This is especially important considering their age, which is a transitional period from childhood to adolescence, during which curiosity about the outside world increases. This seminar activity is expected to educate students about dangers they should avoid early on, such as free association, drugs, bullying, and others. Moreover, this study also aims to guide students in discovering their interests and talents as a first step in planning a more focused and meaningful future. The seminar was conducted using an interactive and reflective approach, involving active student participation through discussions, question-and-answer sessions, and encouraging students to reflect on their feelings and experiences to better understand themselves. One session of the seminar included critical listening, directed towards thought-provoking questions that indirectly encouraged students to think critically in answering them. At the end of the seminar, each student was invited to make a personal commitment about the things they should do for a better future.